Nucleosome landscape and control of transcription in the human malaria parasite - Ponts, Nadia; Harris, Elena Y.; Prudhomme, Jacques; Wick, Ivan; Eckhardt-Ludka, Colleen; Hicks, Glenn R.; Hardiman, Gary; Lonardi, Stefano; Le Roch, Karine G. (Genome Research, 2010)
In eukaryotic cells, chromatin reorganizes within promoters of active genes to allow the transcription machinery and various transcription factors to access DNA. In this model, promoter-specific transcription factors bind DNA to initiate the production of mRNA in a tightly regulated manner. In the case of the human malaria parasite, Plasmodium falciparum, specific transcription factors are apparently underrepresented with regards to the size of the genome, and mechanisms underlying transcriptional regulation are controversial. Here, we investigate the modulation of DNA accessibility by chromatin remodeling during the parasite infection cycle. We have generated genome-wide maps of nucleosome occupancy across the parasite erythrocytic cycle using two complementary assays—the formaldehyde-assisted isolation of regulatory elements to extract protein-free DNA (FAIRE) and the MNase-mediated purification of mononucleosomes to extract histone-bound DNA (MAINE), both techniques being coupled to high-throughput sequencing. We show that chromatin architecture undergoes drastic upheavals throughout the parasite's cycle, contrasting with targeted chromatin reorganization usually observed in eukaryotes. Chromatin loosens after the invasion of the red blood cell and then repacks prior to the next cycle. Changes in nucleosome occupancy within promoter regions follow this genome-wide pattern, with a few exceptions such as the var genes involved in virulence and genes expressed at early stages of the cycle. We postulate that chromatin structure and nucleosome turnover control massive transcription during the erythrocytic cycle. Our results demonstrate that the processes driving gene expression in Plasmodium challenge the classical eukaryotic model of transcriptional regulation occurring mostly at the transcription initiation level.